Factors that Influence Employee Early Retirement Decision Making in the HR Unit of PT. Telekomunikasi, Tbk Bandung - Maharani, Putie; Inarie, Yefke Inarie; Zakharia, Anantha (Formosa Journal of Applied Sciences, 2024)
Companies must be careful in managing early retirement policies. In designing, implementing and administering it. If the company does not do it properly, problems will arise for the company. For example, many employees retire early while they are still needed by the company. This research is aimed at examining the extent to which these four factors can change employees' intentions in making decisions to retire early. Using the case study method of PT. Telekomunikasi Indonesia Bandung HR unit. The research method uses binary number calculations. For the instrument, a questionnaire was distributed to 50 respondents. The variables studied are differences in personal interests (difference variables) and organizational factors which significantly influence the intention to participate in an early retirement program. Meanwhile, opportunities in career paths and external factors have little influence on employees' intentions to take early retirement.